CFD study of the hull-propeller interaction in marine vehicles under different sailing conditions - عباس, نوار (Latakia University Journal -Engineering Sciences Series, 2024)
This research used CFD technology to study the hull-propeller interaction of two different types of marine craft under different sailing conditions (with and without drift angle). The study was conducted on a JBC (Japan Bulk Carrier) and DARPA Suboff submarine models. Initially, a comparison was made between the numerical and the available experimental results for the total resistance and velocity field to ensure the accuracy of the CFD settings and equations used. The comparison confirmed that there was great agreement between the results. The ship and the submarine were then studied alone without the propeller, aiming to know and analyze the velocity, pressure, and vortex field around the marine craft without the propeller. Then, the propeller was added, and the effect of the presence of the working propeller on the characteristics of the flow field and the formed vortex system was studied. The URANS (Unsteady Reynolds Averaged Navier Stokes Equations) method and the K-Ꞷ SST turbulence model were used to solve the Navier Stokes equations within the ANSYS program, in addition, the mesh motion feature was used to calculate the interaction between the hull and the propeller.